Correction: Chen et al. Metabolomics-Based Study on the Anticonvulsant Mechanism of Acorus tatarinowii: GABA Transaminase Inhibition Alleviates PTZ-Induced Epilepsy in Rats. Metabolites 2025, 15, 175 - Liang Chen; Jiaxin Li; Chengwei Fang; Jiepeng Wang (Metabolites)
Error in Figure [...]